I’LAL BIL IBDAL PADA FI‘IL MADI DAN FI‘IL MUDARI‘ DALAM KITAB JAWAHIRUL KALAMIYYAH: KAJIAN LITERATUR MORFOLOGI ARAB: POLA I‘LĀL BI AL-IBDĀL PADA FI‘L MĀḌĪ DAN FI‘L MUḌĀRI‘ DALAM KITAB JAWĀHIR AL-KALĀMIYYAH - Ikhfanul Chakiki; Asep Sunarko; Ahmad Zuhdi (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2026)
Arabic morphology or ṣarf, has a regular system of word formation, one of which occurs through the process of i‘lāl bi al-ibdāl, namely the substitution of letters in certain morphological environments. This study aims to identify the forms of i‘lāl bi al-ibdāl in fi‘l māḍī and fi‘l muḍāri‘ in Kitab Jawāhir al-Kalāmiyyah and to explain the rules governing their changes. This study employs a qualitative approach with library research as its research type. The data were collected through documentation and analyzed using content analysis and morphological analysis. The results show that there are 115 occurrences of i‘lāl bi al-ibdāl, consisting of 82 occurrences in fi‘l māḍī and 33 occurrences in fi‘l muḍāri‘. In fi‘l māḍī, the findings include 58 cases of thulāthī mujarrad, 16 cases of thulāthī mazīd biharfin,and 8 cases of thulāthī mazīd biharfaini. In fi‘l muḍāri‘, the findings include 20 cases of thulāthī mujarrad, 9 cases of thulāthī mazīd biharfin, and 4 cases of thulāthī mazīd biharfaini. The forms of change found include the substitution of yā’ into alif, wāw into alif, hamzah into alif, wāw into tā’, and tā’ into dālaccompanied by idghām. These findings indicate that i‘lāl bi al-ibdāl in Kitab Jawāhir al-Kalāmiyyah occurs systematically and in accordance with the rules of ṣarf.